If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -40y = 0 Solving 15x + -40y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40y' to each side of the equation. 15x + -40y + 40y = 0 + 40y Combine like terms: -40y + 40y = 0 15x + 0 = 0 + 40y 15x = 0 + 40y Remove the zero: 15x = 40y Divide each side by '15'. x = 2.666666667y Simplifying x = 2.666666667y
| 8(3w+5)=-9 | | 0.4(2x+8)-0.4x=0.2(4x-12)+6x | | (x^y^3/x^3y^-4)^2 | | 751=1.5x+5y+y+x+(0.5x-17) | | (x^y^3/x^3y^-4) | | 12n-12=7 | | D(p)=147-p^2 | | 12-6x=-48 | | 4x+31-x=40 | | 0=xsquared-7x+12 | | -6(n+6)=24+6n | | 6r-2=-6r-26 | | .5r+.5s=3 | | 10x^2=10x+23 | | (x-3)2+2x=14 | | -9=-4p+3 | | 19.2=4p+2 | | 40=7x+4y | | -8+5x=3+8x+1 | | 2=0.25j+0.50 | | 4.5x=1 | | 27=1.5x | | (20-4X)/4 | | x^2+24x+19= | | 6h-3=4h+15 | | 20-4X/4 | | 5.4d-2.3d+3(d-4)=6.5 | | x/8-3=7 | | f(x)=4x+x^3 | | 5b+7=7b-6 | | M-5=-2m+16 | | 11.2=2p+3 |